2012
DOI: 10.1016/s1734-1140(12)70870-8
|View full text |Cite
|
Sign up to set email alerts
|

Kynurenic acid enhances expression of p21 Waf1/Cip1 in colon cancer HT-29 cells

Abstract: Abstract:Background: Kynurenic acid (KYNA), a tryptophan metabolite, was found in the mucus of rat small intestine. However, its role in the gastrointestinal tract is still not fully elucidated. Methods: To verify whether KYNA affects cell cycle regulators, the protein expression of cyclin-dependent kinase inhibitor p21 Waf1/Cip1 was investigated in colon adenocarcinoma HT-29 cells exposed to KYNA. MTT, BrdU assay and siRNA technology were used to evaluate the effect of KYNA on cancer cell proliferation. Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
39
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 31 publications
(45 citation statements)
references
References 20 publications
6
39
0
Order By: Relevance
“…Akt is also a negative regulator of CDK inhibitors p21 Waf1/Cip1 and p27 Kip1 (Gesbert et al 2000; Zhou et al 2001). The results suggested that Akt inhibition in KYNA-treated HT-29 cells might result in previously reported overexpression of p21 Waf1/Cip1 (Walczak et al 2012a). Interestingly, KYNA modulated also phosphorylation of GSK3β in HT-29 cells.…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…Akt is also a negative regulator of CDK inhibitors p21 Waf1/Cip1 and p27 Kip1 (Gesbert et al 2000; Zhou et al 2001). The results suggested that Akt inhibition in KYNA-treated HT-29 cells might result in previously reported overexpression of p21 Waf1/Cip1 (Walczak et al 2012a). Interestingly, KYNA modulated also phosphorylation of GSK3β in HT-29 cells.…”
Section: Discussionsupporting
confidence: 56%
“…Previous studies indicated antiproliferative properties of KYNA towards colon adenocarcinoma HT-29, Caco-2 and LS-180 cells (Walczak et al 2011, 2012a), renal cell carcinoma Caki-2 cells (Walczak et al 2012b) and glioblastoma T98G cells (Walczak et al 2014). However, the exact molecular mechanism of antiproliferative activity of KYNA has not been fully revealed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Twenty five µl of RT-PCR mixture contained 10 µl of RNase free H O, 5 µl of 5 × buffer, 2 µl of 10 mM dNTP, 100 nmol/l of each primer and 1 µg RNA. The following primers were employed in semi-quantitative RT-PCR analysis: p21 [24,30] forward primer: 5'-AGCAGAGGAAGA-CCATGTGGAC-3' and p21 reverse primer: 5'-TTT-CGACCCTGAGA GTCTCCAG-3' p53 forward primer: 5'-TGCGTGTGGAGTATTTG GATG-3' and p53 reverse primer: 5'-TGGTACAGTCAGAGCCAA-CCAG-3'; b-actin [5] forward primer: 5'-AACAGT-CCGCCTAGAAGCAC-3' and b-actin reverse primer: 5'-CGTTGACATCGTAAAGACC-3'. The amplified products were size-fractionated by electrophoresis on 1.5% agarose gel, and analyzed by a FluorChem 8000 system with a software (Alpha Innotech, Santa Clara, CA, USA).…”
Section: Semiquantitative Rt-pcrmentioning
confidence: 99%
“…The most recent studies by our group have revealed the antiproliferative activity of kynurenic acid, another endogenous tryptophan metabolite, towards cancer cells, including colon cancer cells (Walczak et al, 2011(Walczak et al, , 2012a. Kynurenic acid was found in human body fluids (Kuc et al, 2006(Kuc et al, , 2008Paluszkiewicz et al, 2009;Walczak et al, 2011) as well as in variety of plant and honeybee derived foodstuffs (Turski et al, , 2012Zgrajka et al, 2013).…”
Section: Discussionmentioning
confidence: 99%